একবিংশ শতাব্দীতে রবীন্দ্রচর্চা ও অন্যান্য প্রবন্ধ - ডাইসন, কেতকী কুশারী, ১৯৪০- (কলকাতা : এবং মুশায়েরা, 2010)
Articles chiefly on studies that came up on the life and works of Rabindranath Tagore, 1861-1941, Bengali author, since 1950, from West Bengal and other places in India and outside India, which could be trend-setters for research on him in the 21st century.
Donated by Akbar Ali Khan
In Bengali; includes passages in English.
Keywords: Tagore, Rabindranath, -- 1861-1941 -- 20th century; Tagore, Rabindranath, -- 1861-1941 -- Criticism and interpretation -- History -- 20th century; Tagore, Rabindranath, -- 1861-1941 -- Criticism and interpretation -- Research